PELATIHAN DAKWAH MODEL ADDIE DALAM MENUMBUHKAN EKONOMI KREATIF MELALUI PENANAMAN HIDROPONIK DARI BARANG BEKAS - Aep Kusnawan; Ahmad Muslikhun (Anida (Aktualisasi Nuansa Ilmu Dakwah), 2021)
ABSTRACTThis study aimed to introduce and train hydroponic vegetable cultivation for young people and youth of Larangan. The ADDIE Model method is used (Analysis, Design, Development, Implementation, Evaluation). The training results show that the participants who are trained in entrepreneurship have the potential to empower the surrounding community. They can benefit from developing hydroponics that does not require large land areas, balanced nutrition, free of weeds, and high production. Hydroponics can also take advantage of the yard of the house. Therefore, the younger generation can create breakthroughs and open new jobs in the agricultural sector by holding this activity. They can create and develop a creative economy to be distributed to the broader community. Da'wah training based on the creative economy through hydroponic planting from used goods has shown a new passion among youth and youth in the Larangan sub-district.